PENGARUH MEDIA SOSIAL (INSTAGRAM) TERHADAP BRAND AWARENESS MINUMAN BOBA XIBOBA di INDONESIA - Yuliana Yuliana; Natalia Natalia (Jurnal Ilmiah Hospitality, 2022)
This study aims to determine the influence of Instagram social media on brand awareness of boba drink products which are currently very popular. This study uses a quantitative approach. Data collection was carried out using primary data collection through questionnaires, and secondary data collection by analyzing scientific articles. The population of this study was taken from the total followers of the boba drink Xiboba Instagram account in Indonesia. Determination of the sample was taken using the Taro formula, and the sampling technique used purposive sampling technique. The analysis technique used is Simple Linear Regression Analysis. The results showed that there was a positive and significant influence of social media Instagram on brand awareness of boba drinks in Indonesia.